2018
DOI: 10.1002/mrd.22962
|View full text |Cite
|
Sign up to set email alerts
|

Regionally distinct patterns of STAT3 phosphorylation in the seminiferous epithelia of mouse testes

Abstract: In mouse testes, Sertoli cells support the continuous process of spermatogenesis, which is dependent on seminiferous epithelial cycles along the longitudinal axis of the seminiferous tubule. Sertoli cell function is modulated partly by local cytokines and/or growth factors derived from adjacent tissues such as blood vessels, macrophages, rete testis, etc. However, the spatial activation patterns by local signals in vivo remain unclear. In this study, we focused on Signal Transducers and Activators of Transcrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 40 publications
2
15
0
Order By: Relevance
“…CDH1 is a component of adherens junctions prominently expressed in epithelial tissues (Schneider & Kolligs 2015). The previous study (Nagasawa et al 2018) and our current findings demonstrated that the only somatic cells expressing CDH1 in the mouse testis were epithelial cells of the rete testis. The third marker examined, KRT8, in pair with KRT18, forms intermediate filaments in many simple epithelia (Owens & Lane 2003).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…CDH1 is a component of adherens junctions prominently expressed in epithelial tissues (Schneider & Kolligs 2015). The previous study (Nagasawa et al 2018) and our current findings demonstrated that the only somatic cells expressing CDH1 in the mouse testis were epithelial cells of the rete testis. The third marker examined, KRT8, in pair with KRT18, forms intermediate filaments in many simple epithelia (Owens & Lane 2003).…”
Section: Discussionsupporting
confidence: 71%
“…We also performed immunofluorescent staining for acetylated alpha-tubulin (ace-TUB), which has been reported to be a marker of SCs from the transitional zones (Nagasawa et al 2018). At 1 day of culture, most Figure 2 Characterization of adult and immature SLCs.…”
Section: Adult and Immature Slcs Express Pax8 Cdh1 And Krt8mentioning
confidence: 99%
“…In contrast to TZ SCs, AKT activity in the SCs of the seminiferous tubules changes cyclically, achieving a maximum at stages II-VI of the spermatogenic epithelial cycle and a minimum at stages IX-XII. Thus, phosphorylated (p-AKT) is a molecular marker of the TZ region, as is the phosphorylated signal transducer and activator of transcription 3 (p-STAT3, Nagasawa et al, 2018) reported previously.…”
Section: Functions Of the Adult Mousesupporting
confidence: 52%
“…Furthermore, although transient-amplifying spermatogonia in the mouse testis can fragment and contribute to the spermatogonial stem cell pool (Nakagawa et al, 2010), whether JAK/STAT signaling is involved in this process during homeostasis or stress is not known. It has been shown that activated Stat3 in the mouse testis is concentrated in somatic Sertoli cells that support undifferentiated spermatogonial cells, consistent with the expression pattern of activated Stat92E in the Drosophila testis (Nagasawa et al, 2018). What activates Stat3 and its specific roles in Sertoli cells are not entirely clear.…”
Section: Introductionmentioning
confidence: 79%